ISLAMIC VALUE-BASED STRATEGIC PLANNING : A STUDY OF SHARIA-COMPLIANT RURAL BANKS IN INDONESIA - Dira Abdi (GREET, 2024)
This study examines how Islamic value-based strategic planning is applied in Sharia-compliant rural banks in Indonesia and how it helps these banks grow sustainably and gain the trust of their communities. Using qualitative methods combined with data from reports and case studies, the research shows that applying Islamic values like justice, transparency, and social welfare improves the banks’ operations and builds strong customer loyalty, especially in rural areas where ethical and community ties are very important. The study also finds that involving the community through education programs helps increase financial knowledge and attract new customers. Despite challenges such as following regulations and facing competition, these banks have adapted well by using technology like fintech, especially during the COVID-19 pandemic. This research fills a gap in understanding how Islamic principles influence banking strategies and provides useful advice for bank leaders and policymakers to develop ethical and inclusive financial systems based on these values.